The Influence of Professional Subculture on Information Security Policy Violations: A Field Study in a Healthcare Context - Sarkar, Sumantra; Vance, Anthony; Ramesh, Balasubramaniam; Demestihas, Menelaos; Wu, Daniel Thomas (Information Systems Research, 2020)
The Influence of Professional Subculture on Information Security Policy Violations: A Field Study in a Healthcare Context